2020
DOI: 10.3390/catal10040404
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fine-Tuning Redox Potentials of Manganese(II) Complexes with Isoindoline-Based Ligands: H2O2 Oxidation and Oxidative Bleaching Performance in Aqueous Solution

Abstract: A series of divalent manganese complexes [M II (HL 1-6 )Cl 2 ] with the 1,3-bis(2'-Ar-imino) isoindolines (HL n , n = 1-6, Ar = pyridyl, 4-methylpyridyl, imidazolyl, thiazolyl, benzimidazolyl and N-methylbenzimidazolyl, respectively) including the previously reported ligands (HL 1-2, 4-6 ) and complexes ([M II (HL 1,5 )Cl 2 ]) have been prepared and characterized by electrochemical and spectroscopic methods. In these complexes, it was possible to control the redox potential of the metal center by varying the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…When potassium persulfate increased to 5% of the mass of acrylic acid, the chelated iron value reached the maximum, it indicated that the amount of initiator met the requirements of the polymerization, and the number of free radicals generated was enough to initiate the monomer polymerization. The potassium persulfate dosage increased to 6%, the chelated iron value decreased significantly, indicated that excessive initiator increased the crosslinking degree of monomers, decreased the sensitivity and reduced the chelating performance 33 . The chelated calcium value hardly fluctuated, indicating that initiator dosage had little effect on chelated calcium value.…”
Section: Resultsmentioning
confidence: 99%
“…When potassium persulfate increased to 5% of the mass of acrylic acid, the chelated iron value reached the maximum, it indicated that the amount of initiator met the requirements of the polymerization, and the number of free radicals generated was enough to initiate the monomer polymerization. The potassium persulfate dosage increased to 6%, the chelated iron value decreased significantly, indicated that excessive initiator increased the crosslinking degree of monomers, decreased the sensitivity and reduced the chelating performance 33 . The chelated calcium value hardly fluctuated, indicating that initiator dosage had little effect on chelated calcium value.…”
Section: Resultsmentioning
confidence: 99%
“…The ligands 1,3-bis(2 -Ar-imino)isoindolines (HL n , n = 1-6, Ar = 4 -methyl-pyridyl, pyridyl, imidazolyl, thiazolyl, benzimidazolyl and Nmethylbenzimidazolyl, respectively) and their complexes [Mn II (HL 1−6 )Cl 2 ] (1-6) were prepared according to published procedures (Scheme 1) [12,18]. GC analyses were performed on an Agilent 6850 gas chromatograph equipped with a flame ionization detector and 30 m SUPELCO BETA DEX225 columns.…”
Section: Methodsmentioning
confidence: 99%
“…Based on our previous experience we expected that varying the aryl group on the bisiminoisoindoline moiety would directly tune electron density in the metal center and hence allow us to evaluate the influence of these electronic changes on reactivity. Cyclic voltammetry measurements on complexes 1-6 reveal that the Mn(III/II) redox potentials can vary by up to 560 mV between the most electron-withdrawing (948 mV for 1) and the most electron-donating (388 mV for 5) [18]. With a systematic series of [Mn II (HL 1−6 )Cl 2 ] (1-6) complexes, we investigated their oxidative reactivity for HAT (hydrogen atom transfer) and OAT (oxygen atom transfer) reactions with benzyl alcohol and thioanisole.…”
Section: Catalytic Oxidation Of Benzyl Alcoholsmentioning
confidence: 99%
See 2 more Smart Citations